Virtual Crack Closure Technique on Delamination Fracture Toughness of Composite Materials Based on Epoxy Resin Filled with Micro-Scale Hard Coal - Uysal, M. Uslu (POLISH ACAD SCIENCES INST PHYSICS, 2017)
In the present paper, the delamination fracture toughness of composite materials on cantilever beams was studied. The cantilever beams were assumed to be epoxy resin filled with hard coal and recently developed a new composite material model was used. Accordingly, the composite materials were based on epoxy resin as a matrix and two types of hard coal as fillers with additions of 4.32, 7.5, and 10.68 vol.%. The fracture toughness of epoxy-hard coal composite cantilever beams was investigated numerically by using ANSYS (R) finite element analyses package program. Mode I fracture toughness (critical strain energy release rate) in the neighborhood of the crack zone was found by using virtual crack closure technique for critical displacement values. The influences of the types and volumes of the hard coal fillers on the strain energy release rate were presented. The critical strain energy release rate increased at 10.8% when the volume ratio of anthracite coal was increased from 4.32% to 10.68%. Model verification of the finite element analysis was performed with an analytical solution in literature and the difference was determined as 3.75% and also this pointed the precision of the present finite element analysis.
Keywords: STRESS INTENSITY FACTORS; Physics